Staphylococcus aureus Alpha-Hemolysin Impairs Corneal Epithelial Wound Healing and Promotes Intracellular Bacterial Invasion - Putra, Ilham (Exp Eye Res, 2019)
Colonization by Staphylococcus aureus (S. aureus) has been implicated in many infectious and wound healing disorders. This study was performed to characterize the pathogenic role of S. aureus alpha-hemolysin (alpha-toxin) in corneal epithelial wound healing and infectious keratitis in the setting of a corneal wound. The effect of wild-type and isogenic Hla mutant (α-hemolysin gene deleted) S. aureus bacteria and conditioned media on corneal epithelial wound healing was tested in vitro using a scratch assay and in vivo using a murine epithelial debridement model. The invasiveness of wild-type and Hla mutant S. aureus was evaluated in vitro in human corneal epithelial cells and in vivo in a murine model of infectious keratitis following total epithelial debridement. S. aureus and its conditioned media significantly delayed epithelial wound closure both in vitro (P<0.05) and in vivo (P<0.05). The effect of S. aureus on wound healing was significantly diminished with the Hla mutant strain (P<0.05). Likewise, compared to the wild-type strain, the Hla mutant strain demonstrated significantly reduced ability to invade corneal epithelial cells in vitro (P<0.05) and infect murine corneas following total epithelial debridement in vivo (P<0.05). In conclusion, S. aureus alpha-hemolysin plays a major role in the pathologic modulation of corneal epithelial wound healing and the intracellular invasion of the bacteria. Limiting colonization by S. aureus and/or blocking alpha-hemolysin may provide a therapeutic approach for corneal wound healing and infectious disorders.